PERAN ARTIFICIAL INTELLIGENCE DALAM MANAJEMEN INFORMASI KESEHATAN UNTUK OPTIMALISASI STRATEGI BISNIS DIGITAL - M. Syahputra; Amalia Hanifa; Andri Swandi; Imrah Sari; Anita Citra Yeni (Smart Education, 2026)
The development of Artificial Intelligence (AI) has brought significant transformations in various sectors, including health information management. The integration of AI in health data management not only improves operational efficiency but also opens up strategic opportunities in digital business development in the healthcare sector. This study aims to analyze the role of AI in health information management and its impact on optimizing digital business strategies. The method used is a qualitative approach with a systematic literature review of various recent scientific publications (2020–2025) relevant to the research topic. Data were analyzed using thematic analysis techniques to identify patterns, trends, and contributions of AI in health information management. The results show that the application of AI, such as machine learning, natural language processing, and predictive analytics, can improve data processing accuracy, accelerate decision-making, and support personalized healthcare services. In addition, AI plays a role in increasing operational cost efficiency and creating innovative digital business models, such as telemedicine and intelligent-based electronic medical record systems. However, challenges related to data security, patient privacy, and infrastructure and human resource readiness remain major obstacles to its implementation. In conclusion, AI has a strategic role in improving the quality of health information management while strengthening the competitiveness of digital businesses in the healthcare sector. Therefore, adaptive policies, improved human resource competencies, and strengthened information security systems are needed to support the sustainable implementation of AI.